A Curriculum for Master of Science in Physiology of Mbarara University of Science and Technology in Uganda - Betancourt Valladares, Miriela; Balaam, Kasiisi; Rosemary, Namayanja; James Mukasa, Kiguli; Cadenas-Freizas, José Luis; Domínguez Montero, Genny (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: There are differets ways to design a Curriculum for Master of Science in Physiology to train postgraduate students. Objective: to design a Curriculum for Master of Science in Physiology to train postgraduate students in Mbarara University of Science and Technology (MUST) of Uganda. Methods: MUST was founded in 1989 and its Academic programmes are intended to be tailored towards the Government effort of solving Uganda’s economic problems by producing the skilled manpower in all relevant areas. There are 7 Degree programmes and 12 Master’s Degree Programmes, one of which was Physiology. The Department of Physiology was a pioneer in the Faculty of Medicine and had been training postgraduate students for some time without a proper curriculum. New regulations and guidelines together with the development of science and teaching demanded to generate a new Curriculum for Master in Physiology in order to resume the training at MUST according to the current needs and standards. During one year and under the guidance of the Curriculum Committee Faculty of Medicine, different steps were followed to come up with a product able to satisfy the requirements. Accomplished tasks included: identification of mandatory courses based on the need of a physiologist with knowledge in all areas to be able to train undergraduates through Physiology with research and teaching skills; a large search of curricula followed by several universities in Uganda and abroad; several meetings, discussions, workshops to review contents, objectives, skills and the overall structure according to the guidelines, and review after submissions. Results: The curriculum was designed, presented, reviewed at the different established levels and approved to resume the training of postgraduate students in the area of Physiology by the Department of Physiology, Faculty of Medicine, MUST. The first group of postgraduates started their training following this curriculum in August 2016. Conclusions: As a result of the request by the Dean, Faculty of Medicine, MUST; the efforts made by the Physiology staff members who directly participated in designing the curriculum, under the leadership of the Head of Department who spent 4 years working as staff of the University; with the invaluable guidance of the Curriculum Committee, MUST; and the support and mentorship from experienced colleagues; was possible to come up with a curriculum in less than one year. Without this curriculum, the training of Physiologists at MUST was not going to be possible despite the urgent needs of the country.